2016
DOI: 10.1515/jvetres-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Identification of bacterial pathogens and determination of their antibacterial resistance profiles in some cultured fish in Turkey

Abstract: Introduction: In the present study, some of the commercial fish farms located in the Black Sea region of Turkey, were screened for bacteria between 2012 and 2014. Material and Methods: The bacterial agents isolated from fish were identified by classical biochemical tests and the rapid diagnostic tests (API 20 E and API 20 Strep). All strains were further identified by sequencing of the 16S rRNA genes. The strains were also investigated for resistance to different antimicrobials by the disc diffusion method. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
0
18
0
1
Order By: Relevance
“…The antibiotic susceptibility may vary according to the many factors including bacterial species and isolation area. Florfenicol is a relatively new antibiotic, and it has successfully been used for the treatment of bacterial fish diseases in Turkey (Kayis et al 2009;Ture et al 2016). Therefore, the fish were treated with florfenicol in this case of C. freundii infection.…”
Section: Discussionmentioning
confidence: 99%
“…The antibiotic susceptibility may vary according to the many factors including bacterial species and isolation area. Florfenicol is a relatively new antibiotic, and it has successfully been used for the treatment of bacterial fish diseases in Turkey (Kayis et al 2009;Ture et al 2016). Therefore, the fish were treated with florfenicol in this case of C. freundii infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, amplification products obtained from highly conserved 16S rRNA gene as well as their nucleotide sequence homologies with the reference strain Lg2 confirmed that all isolates were L. garvieae. It is known that API test systems enable the identification of many species with high accuracy (Türe & Alp, 2016). However, they still remain insufficient to distinguish between closely related species.…”
Section: Discussionmentioning
confidence: 99%
“…Turkey is one of the biggest fish producers among European countries according to the Turkish Statistical Institute data (TUIK, 2015). Like in the other large-scale producers, bacterial infectious diseases are spreading among fish farms, and antimicrobial treatments are inadequate for the health management (Türe & Alp, 2016). An excessive and incorrect usage of antibiotics for the control of lactococcosis in fish farms has led to an increase in acquired antibiotic resistance which has negative effects on animal and human health (Cabello, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scientific studies indicate that several diseases were affecting wild fish populations before the aquaculture industry existed (Olivier, 2012). The studies related to fish diseases such as pseudomoniasis,pasteurellosis, motile Aeromonas septicemia and lactococcosis generally focused on the reared fish species in Turkey (Korun & Timur, 2005;Onuk et al 2015;Ture & Alp, 2016). On the other hand, Nishizawa et al (2006) investigated to detection of viral hemorrhagic septicemia virus from wild turbot (Psetta maxima) in a Turkish coastal area.…”
Section: Introductionmentioning
confidence: 99%